Singularity of Spatial 3-PRR Parallel Mechanism and Its Application in Irregular Surface Engraving Machine - Bin Sun; Ruiqin Li; Jingjing Liang (Jixie chuandong)
A spatial 3-PRR parallel mechanism is proposed and the axes of all the revolute pairs of the parallel mechanism are parallel to each other. Based on the screw theory calculation，the mechanism has three degrees of freedom （DOFs） which include two translations and one rotation. The inverse kinematic solutions are obtained by using close-loop vector method. Based on the inverse kinematic solutions，the Jacobian matrix of the mechanism is solved，and two kinds of singularities of the mechanism are obtained according to the Jacobian matrix. Based on the given parameters and constraints，the reachable workspace of the moving platform is determined by using workspace search method. An application example of engraving machine for irregular surface is given. The experiment result shows that its performance can satisfy the requirements of engraving.